Mechanical Properties of Hybrid Polymer Composite Using Natural Fiber and Nanoparticle. (April 2019) - Kai, C. W.; Abdullah, A.H.; Debnath, S.
Abstract: Hybrid polymer composite were prepared by incorporating two indigenous agro-industrial waste reinforcements, sugarcane bagasse fiber (SBF) and coconut coir fiber (CCF) into epoxy resin through the hand lay-up technique. Nano-silica was also added to enhance the mechanical performance of composite materials. The alkaline treatment on the surface of natural fibers was carried out and its effects on the mechanical properties were investigated. Generally, it is found that the CCF reinforced epoxy composites exhibited higher mechanical properties as compared to the SBF reinforced epoxy composites. For hybrid composite samples, (2.5wt%SBF+12.5wt%CCF) had attained the highest mechanical performance amongst all other different ratio percentage of hybrid polymer composite.